2020
DOI: 10.1021/acs.jafc.9b06937
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Action of Novel Pyrazole Carboxamide Containing a Diarylamine Scaffold against Rhizoctonia solani

Abstract: In the last few decades, Rhizoctonia solani causing rice sheath blight has resulted in a lot of economic losses in the world. Therefore, many novel pyrazole carboxamide fungicides have been intensively researched and employed to fight against it. In this regard, in recent years, our group reported a novel pyrazole carboxamide containing a diarylamine scaffold with good antifungal activity against rice sheath blight in the pot test and field trial. Following this project, the antifungal mechanism of action of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 41 publications
2
25
0
Order By: Relevance
“…For instance, the increase of the cell membrane permeability may be caused by ultrastructure damages in cell walls or cytomembrane structures. Another research found that a compound probably targeting respiratory electron transport players could also destroy the cell walls or membranes of R. solani . This might be a similar mechanism that ultrastructure was damaged in our study.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…For instance, the increase of the cell membrane permeability may be caused by ultrastructure damages in cell walls or cytomembrane structures. Another research found that a compound probably targeting respiratory electron transport players could also destroy the cell walls or membranes of R. solani . This might be a similar mechanism that ultrastructure was damaged in our study.…”
Section: Discussionsupporting
confidence: 71%
“…Another research found that a compound probably targeting respiratory electron transport players could also destroy the cell walls or membranes of R. solani. 37 This might be a similar mechanism that ultrastructure was damaged in our study. In addition, exogenously supplemented ATP could weaken the inhibitory activity of SYP-34773 against P. infestans to certain degrees, especially for zoospore release and cyst germination.…”
Section: ■ Discussionsupporting
confidence: 66%
“…DMSO was used as the blank control. The morphology and ultrastructure of mycelia were observed by a scanning electron microscope (Hitachi, Ltd., Tokyo, Japan) and a transmission electron microscope (JEOL, Ltd., Tokyo, Japan). , …”
Section: Materials and Methodsmentioning
confidence: 99%
“…The morphology and ultrastructure of mycelia were observed by a scanning electron microscope (Hitachi, Ltd., Tokyo, Japan) and a transmission electron microscope (JEOL, Ltd., Tokyo, Japan). 9,20 Effect of Compound 3e on the Cell Membrane Permeability of F. oxysporum. The effect of compound 3e on the permeability of the cell membrane of F. oxysporum was determined by the conductivity method.…”
Section: N T N Mycelial Growth Inhibition Rate (%) (mentioning
confidence: 99%
“…2.12 Effects of zeylenone on the mycelium ultrastructure of Phytophthora capsici by transmission electron microscopy Zeylenone was mixed with potato dextrose broth (PDB) medium to make the final concentration of 7 μg mL −1 , and the corresponding solvent was used as the control. The Phytophthora Phytophthora capsici plugs were cultured with shaking at 25 °C, 120 rpm for 72 h. 30 The mycelium samples were fixed in 4% glutaraldehyde buffer fixation solution at 4 °C overnight, and washed three times in 0.1 mol L −1 phosphate-buffered saline (PBS) buffer (pH 7.0) for 15 min each time. 31 Then the mycelium samples were dissolved in 1% osmium tetroxide buffer fixative solution at room temperature and fixed for 2 h. The mycelium samples were washed four times with 0.1 mol L −1 PBS buffer (pH 7.0) for 10 min each time.…”
Section: Effect Of Zeylenone On the Myceliummorphology Of Phytophthora Capsici By Optical Microscopymentioning
confidence: 99%